Keberadaan Perempuan pada Organ Corporate Governance dan Risiko Kredit Perbank Indonesia - Reza, Oktavieni Medya; Zaitul, Zaitul (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to empirically prove the influence of women on the board of commissioners, board of directors, and audit committees on credit risk in banking companies listed on the Indonesia Stock Exchange. In this research, 19 banking companies were used based on special criteria that we set. The study was conducted from 2021 to 2022. The data analysis method was multiple linear regression (OLS) and t-statistical testing. Following the results of hypothesis testing, it was found that the presence of women on the board of commissioners, and audit committee was proven to have a negative and significant effect on credit risk in banking companies on the Indonesia Stock Exchange. These results show that the presence of women on the board of commissioners, and audit committee is able to encourage credit distribution governance in each bank and provide higher information transparency to stakeholders. This positive thing has encouraged the reduction of credit risk in banking companies on the Indonesia Stock Exchange, which can be seen from changes in the non-performing loan ratio held by each bank.